A Wideband Sub-GHz Receiver Front-end Supporting High Sensitivity and Selectivity Mode - 남일구; 이옥구; Donggu Im (Journal of semiconductor technology and science, 2021)
A low noise and highly linear wideband RF front-end circuit for sub-GHz Internet of Things (IoT) applications is proposed. The proposed front-end is composed of a broadband single-ended LNA, a wideband differential LNA employing thermal noise cancellation technique, and an in-phase and quadrature (I/Q) linearized harmonic rejection mixer (HRM). Depending on the interference environment, the proposed front-end supports two operation modes having high sensitivity and selectivity performance by enabling or disabling the first building block of the single-ended LNA. At high sensitivity mode, the front-end shows a voltage gain (Av) of greater than 38 dB, a noise figure (NF) of less than 2.1 dB, an input-referred third-order intercept point (IIP3) of greater than -23 dBm, and an input-referred second-order intercept point (IIP2) of greater than +15 dBm in the sub-GHz frequency band. Concerning for high selectivity mode, it achieves an Av of greater than 22.5 dB, a NF of less than 4.7 dB, an IIP3 of greater than –6.8 dBm, and an IIP2 of greater than +50 dBm over the same operating frequency range. KCI Citation Count: 0